Odpowiedź :
[tex]zad.2)\\\\a)\\\\\sqrt[3]{27}=\sqrt[3]{3^3}=3\\\\b)\\\\ \sqrt[3]{-\frac{1}{8}} = \sqrt[3]{(-\frac{1}{2})^3}=-\frac{1}{2}\\\\c)\\\\\sqrt[3]{0}=0\\\\d)\\\\\sqrt[3]{1}=1[/tex]
[tex]e)\\\\\sqrt[3]{-1}=-1\\\\f)\\\\\sqrt[3]{-8000}=\sqrt[3]{(-20)^3}=-20\\\\g)\\\\\sqrt[3]{0,064}=\sqrt[3]{(0,4)^3}=0,4\\\\h)\\\\ \sqrt[3]{1\frac{61}{64}}=\sqrt[3]{ \frac{125}{64}}=\sqrt[3]{ (\frac{ 5}{ 4})^3}=\frac{5}{4}[/tex]
Odpowiedź:
Szczegółowe wyjaśnienie:
a/ = 3
b/ = -1/2
c/ = 0
d/ = 1
e/ = -1
f/ = -20
g/ = 0,8
h/ = ³√125/64 = 5/4 = 1 i 1/4